A Miniaturized Wideband Planar Bow-Tie Slot Antenna with Asymmetric CPW. (5th July 2022) - Chen, Xi; Huang, Jiasong; Cheng, Chonghu; Liu, Leilei
Abstract : In this paper, a novel miniaturized wideband planar bow-tie slot antenna is proposed. For the purpose of miniaturization and wide bandwidth, the effects of the dimension and shape of the bow-tie slot and feed structure are analyzed. This antenna adopts a water droplet slot, fed by an optimized asymmetric coplanar waveguide (CPW). By adjusting the feeding line, the impedance characteristic of the antenna is greatly improved that leads to a broader bandwidth. The proposed antenna operates from 2.8 GHz to 5.25 GHz with a gain of 3.8 dB. Compared with the traditional triangle bow-tie antenna, the relative bandwidth of the proposed antenna is broadened to more than 61%, while the size is reduced by about 36%, which indicates the proposed antenna is suitable for a variety of wireless applications.